The Comparative Parliamentary Democracy Data Archive - Bergman, Torbjörn; Strøm, Kaare; Müller, Wolfgang (Södertörn University, 2011)
The Comparative Parliamentary Democracy Data Archive data set consist of cabinet-level data of 17 Western European democracies for post-WWII cabinets through January 1, 1999. All together, a total of 424 coalitions, single party and non-partisan cabinets are included. Data for Greece, Portugal and Spain exist only after their democratizations in the 1970s, while data on France is limited to the Fifth Republic beginning in 1959. For the purposes of our data set, it can be said that the world "froze" on January 1, 1999. The last observation in each country is coded on the basis on the information that was available on that day.

Purpose:

The Comparative Parliamentary Democracy project examines West European parliamentary politics from a principal–agent perspective.

The ZIP file consist sav files (for SPSS) and documentation in pdf format (codebooks).

Datasetet i "The Comparative Parliamentary Democracy Data Archive" består av data på regeringsnivå för 17 västeuropeiska demokratier från 1945 till och med 1 januari 1999. Totalt ingår 424 olika koalitions-, enpartis- och partiobundna regeringar. Data från Grekland, Portugal och Spanien finns enbart från tiden efter demokratiseringen av dessa länderna under 1970-talet, medan data från Frankrike är begränsad till den femte republiken med start 1959. För detta dataset kan man säga att världen "frös" den 1 januari 1999. De sista observationerna för varje land är kodad på grundval av den information som fanns tillgänglig detta datum.

Syfte:

Syftet med projektet är att studera västeuropeisk politik utifrån ett "principal-agent"-perspektiv.

Zip-filen innehåller data, på engelska, i sav-format (för SPSS). Filen innehåller även SND-kodböcker (metadata på svenska respektive på engelska) samt två kodböcker producerade av primärforskarna. Samtliga kodböcker i pdf-format.
Önskas annat format av datamaterialet (ex. sas elller stata) kontakta SND.
The Comparative Parliamentary Democracy Data Archive
Keywords: STATE CONTROL; STATLIG STYRNING; GOVERNMENT POLICY; REGERINGSPOLITIK; GOVERNMENT; REGERING; GOVERNMENT ROLE; STATSMAKTENS ROLL; POLITICAL PARTIES; POLITISKA PARTIER; Political behaviour and attitudes; Politiska beteenden och attityder; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap